Identification of Anticancer Drugs Associated With Cancer Therapy‐Related Cardiac Dysfunction in Pediatrics—Analysis of the WHO Pharmacovigilance Database - Labombarda, Fabien; Rouger, Jérémie; Legallois, Damien; Dolladille, Charles; Alexandre, Joachim; Chrétien, Basile (Pediatric Blood & Cancer, 2025)
AIMS: Cardiovascular toxicities associated with anticancer drugs constitute a significant concern for pediatric patients undergoing cancer treatment. Comprehensive data on the burden of cancer therapy-related cardiac dysfunction (CTRCD) are lacking, particularly for this high-risk population susceptible to develop myocardial toxicity. By analyzing VigiBase, the World Health Organization's individual case safety report database, we sought to determine anticancer drugs associated with CTRCD in pediatric patients. METHODS AND RESULTS: To evaluate the association between 249 anticancer drugs labeled by the FDA or EMA and CTRCD reporting, we performed a disproportionality analysis, calculating multivariable adjusted reporting odds ratios (aROR) with their 95% confidence intervals (CI) across four pediatric age classes (0-27 days, 28 days to 23 months, 2-11 years, 12-17 years); ClinicalTrial registration number: NCT05602103. We identified 796 cases of CTRCD associated with at least one anticancer drug in VigiBase. Multivariate analysis across the pediatric age spectrum revealed 16 anticancer drugs significantly associated with CTRCD, of which 10 (63%) are primarily used for hematologic malignancies. Two drugs, a topoisomerase 1 inhibitor (topotecan) and cytotoxic antibiotics (dactinomycin), represented novel associations with CTRCD not previously documented in the literature. CONCLUSION: Within VigiBase, we pinpointed 16 anticancer drugs significantly associated with CTRCD reporting in pediatrics. Our research validated several associations already thoroughly reported in children (such as with anthracyclines), and unveiled novel signals for systemic exposure to topotecan and dactinomycin. The relevance of these findings, especially considering the frequency of co-administration of agents and the lack of information regarding radiation exposure and chemotherapy dosage, would need to be evaluated in the context of clinical trials that use or have used these agents.